TRADITIONAL CRAFTS OF UZBEKISTAN IN MODERN INTERIOR DESIGN - Makhmudova, Malika; Makhmudova, Muhayyo (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article describes the historical development of the decoration of architectural monuments of Uzbekistan, characteristics of ethno-style, the use of traditional crafts and motifs in interior design, regularity of use of ethno-style in a modern architectural environment.Analytical approaches and methods of comparison were used in the article as well as materials of the authors’ researches. In addition, the literature on the Central Asian decor, applied art and crafts of Uzbekistan, interior design in ethno-style and others was studied.